2010
DOI: 10.1093/ejo/cjp144
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial reward of orthodontic treatment in adult patients

Abstract: The purpose of this study was to assess the short-term psychosocial impact of dental aesthetic improvement in adult subjects. Sixty-nine adult patients (61 females and 8 males, aged 21-59 years) requesting aesthetic dental improvement were prospectively and randomly recruited for the study in a private orthodontic office. A general interview included patient motivation and expectations from treatment. After clinical examination, discussion of the mode of treatment and the expected outcome, the patients were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 20 publications
4
54
1
4
Order By: Relevance
“…26 The PIDAQ test measures three dimensions of psychosocial impacts, and is, simply, a reproducible, statistically easy test to use and can be completed in a short time. Studies about PIDAQ should be undertaken in patients undergoing oral restorative treatment in the anterior region 38 and implantation of missing anterior teeth is a very important restorative procedure. In this study, each patient was set up as his/her own control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The PIDAQ test measures three dimensions of psychosocial impacts, and is, simply, a reproducible, statistically easy test to use and can be completed in a short time. Studies about PIDAQ should be undertaken in patients undergoing oral restorative treatment in the anterior region 38 and implantation of missing anterior teeth is a very important restorative procedure. In this study, each patient was set up as his/her own control.…”
Section: Discussionmentioning
confidence: 99%
“…21 PIDAQ contains 23 items, which are established based on the study of dental aesthetic and oral-health-related quality of life. [22][23][24] The reliability, validity and applicability of the PIDAQ for young adults in Brazil has been assessed. 25 Prior work has also shown that the translated Chinese version of PIDAQ demonstrates good reliability, validity and responsiveness.…”
Section: Objectivementioning
confidence: 99%
“…1 The recent increase of esthetic expectations in physical appearance leads individuals from every age group and socioeconomic status to desire orthodontic treatment. In addition, the visibility of orthodontic appliances during active treatment can lead to esthetic concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, patients demonstrate an improvement in self-esteem following treatment [4]. Thus, orthodontic therapy can enhance the patient's psychosocial, subjective sense of well-being [11]. There are various esthetic orthodontic appliances available for orthodontic treatment like ceramic brackets, lingual brackets, clear aligners, etc.…”
Section: Introductionmentioning
confidence: 99%